2017
DOI: 10.1002/adfm.201603998
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Electrochemical Deposition of Large‐Area MoS2 on Graphene for High‐Responsivity Photodetectors

Abstract: Controllable creating of wafer-scale homogeneous vertical or parallel 2D heterostructures with low cost by the van der Waals stacking or covalently bonded stitching of 2D layered materials, such as graphene, hexagonal boron nitride, and transition-metal dichalcogenides, is of great challenge. In this paper, a new green growth strategy for the fabrication of high-quality largearea and low-cost vertical MoS 2 /graphene heterostructures has been successfully demonstrated via electrochemical deposition in water so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 60 publications
(89 reference statements)
0
29
0
Order By: Relevance
“…The well‐established CVD method has been utilized widely to synthesize large‐scale and uniform crystals, such as graphene and TMDs . Different from the exfoliation method, CVD is a bottom‐up method which is essential to large‐scale applications.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…The well‐established CVD method has been utilized widely to synthesize large‐scale and uniform crystals, such as graphene and TMDs . Different from the exfoliation method, CVD is a bottom‐up method which is essential to large‐scale applications.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…The overall resistance (R T ) of the external circuit of the system can be calculated using the following equation. [24]…”
Section: Electroplating Technique Of Mxnss-electromxenitionmentioning
confidence: 99%
“…Recent studies have revealed that 2D materials, such as GO, MoS 2 , and CNT can be easily deposited onto a specific electrode substrate with controlled film morphology and thickness via the electrodeposition method. [21,23,24] Generally, MXNSs have high, negative zeta potentials owing to the surface terminal groups (such as F, OH, and O), which afford their hydrophilic nature and render them suitable for forming stable colloids containing few-layer MXNSs in various polar solvents. [25] Additionally, redox-capable transition metal layers on the surface of MXNSs enable the latter to be used in the electrochemical deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al. used monolayer CVD graphene as the substrate and electrodeposited large‐area, high‐quality vertical MoS 2 , with a thickness of 5–150 nm, onto it from an aqueous solution; this was then annealed in a CVD system . Homogeneous wafer‐scale MoS 2 films on monolayer graphene were achieved with clean and sharp interfaces.…”
Section: Synthesis Of 2d Materialsmentioning
confidence: 99%